1997
DOI: 10.1007/bf02454155
|View full text |Cite
|
Sign up to set email alerts
|

A retrograde double fluorescent tracing study of the levator palpebrae superioris muscle in the cynomolgus monkey

Abstract: In the cynomolgus monkey, motoneurons innervating the levator palpebrae superioris muscle form a nucleus within the oculomotor nuclei called the central caudal nucleus. After double fluorescent neuronal retrograde tracing experiments, using fast blue and diamidino yellow as tracers in the levator palpebrae superior muscles, labelled motoneurons (30%) were found in an unpaired central caudal nucleus. Approximately 2% of the labelled motoneurons were double-labelled. The labelled and double-labelled neurons were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…In lateral-eyed species, such as rabbits, rats, and guinea pigs, the LP nucleus is located more laterally than in frontal-eyed species such as cats and monkeys, in which it forms a caudal and medial subdivision of the oculomotor complex (Porter et al, 1989). Moreover, whereas the innervation of LP in lateral-eyed animals tends to be largely crossed, in cats and monkeys it is bilateral, in the latter even by single LP motoneurons which project to both sides (Hiramoto et al, 1995;VanderWerf et al, 1997). The pigeon is therefore an exception to this ''rule,'' being a lateral-eyed species having a strictly ipsilateral innervation of an eyelid retractor.…”
Section: Vdmentioning
confidence: 96%
“…In lateral-eyed species, such as rabbits, rats, and guinea pigs, the LP nucleus is located more laterally than in frontal-eyed species such as cats and monkeys, in which it forms a caudal and medial subdivision of the oculomotor complex (Porter et al, 1989). Moreover, whereas the innervation of LP in lateral-eyed animals tends to be largely crossed, in cats and monkeys it is bilateral, in the latter even by single LP motoneurons which project to both sides (Hiramoto et al, 1995;VanderWerf et al, 1997). The pigeon is therefore an exception to this ''rule,'' being a lateral-eyed species having a strictly ipsilateral innervation of an eyelid retractor.…”
Section: Vdmentioning
confidence: 96%
“…Afferent innervation of the eyelids and/or extraocular muscles has been extensively studied van Ham and Yeo, 1996a;Billig et al, 1997;May and Porter, 1998;VanderWerf et al, 1997). The present study shows that, after BDA application to the SO nerve and/or microinjections in the upper eyelid, labelled ganglion cells were, as expected, located in the rostral part of the ipsilateral ophthalmic-maxillary portion of the gasserian ganglion.…”
Section: Afferent Eyelid Projectionsmentioning
confidence: 99%
“…Central terminals of these primary neurons are located in the sensory trigeminal complex (Jacquin et al, 1993). Trigeminal afferent innervation of eyelids has been studied in rabbits, guinea pigs, cats, and monkeys (Marfurt, 1981;Holstege et al, 1986;Shigenaga et al, 1986a,b;van Ham and Yeo, 1996a,b;VanderWerf et al, 1997VanderWerf et al, , 1998VanderWerf et al, , 2002May and Porter, 1998). It was found that central terminations were distributed throughout the sensory trigeminal complex, which comprises the nucleus principalis (5P) and the nucleus spinalis further subdivided into pars oralis (5o), pars interpolaris (5i), and pars caudalis (5c).…”
mentioning
confidence: 98%
“…3), both of which have been implicated in eye motor control. [47][48][49][50] The innervation of striatum and superior colliculus by Cg-M2 may also play important roles in motor control. Visual sensory information arriving in Cg-M2 could, therefore, contribute to driving saccadic eye movements and opening of eye-lids in a stimulus-dependent manner.…”
Section: Functional Roles Of Frontal Cortexmentioning
confidence: 99%